Pengembangan Model Pembelajaran Picture And Picture untuk Pembelajaran Menulis Teks Deskripsi VII SMP Negeri 1 Kota Batu - Anggun Restu; Lis Susilawati; Rina Wijayanti; Endang Sumarti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This study was conducted with the aim of making students more active in learning, especially for class VII SMP Negeri 1 Kota Batu. The results of this study indicate that the Picture and Picture learning model developed has very good quality and is suitable for use in learning descriptive texts in class VII SMP Negeri 1 Kota Batu. This model was evaluated through three main aspects: language, material, and design, each of which obtained positive validation results. The language aspect received an average score of 88.88 and was classified as "Very Suitable," indicating that the use of language in this model is appropriate and easy for students to understand. The material aspect obtained an average score of 75, which is classified as "Decent," indicating that the material in the model is adequate but can still be improved. The design aspect obtained an average score of 84.37, also categorized as "Very Decent," indicating that the appearance and visual structure of the model are attractive and in accordance with students' needs. Overall, the Picture and Picture model obtained an average score of 82.75 and is classified as "Very Decent," so it can be implemented as an effective learning medium to improve students' understanding of descriptive texts.